Design and Optimization of Quinazoline Derivatives: New Non-nucleoside Inhibitors of Bovine Viral Diarrhea Virus - Fernández, Gabriela A.; Castro, Eliana F.; Rosas, Rocío A.; Fidalgo, Daniela M.; Adler, Natalia S.; Battini, Leandro; España de Marco, Maria J.; Fabiani, Matias; Bruno, Ana M.; Bollini, Mariela; Cavallaro, Lucia V. (Frontiers in Chemistry, 2020)
Bovine viral diarrhea virus (BVDV) belongs to the Pestivirus genus (Flaviviridae). In spite of the availability of vaccines, the virus is still causing substantial financial losses to the livestock industry. In this context, the use of antiviral agents could be an alternative strategy to control and reduce viral infections. The viral RNA-dependent RNA polymerase (RdRp) is essential for the replication of the viral genome and constitutes an attractive target for the identification of antiviral compounds. In a previous work, we have identified potential molecules that dock into an allosteric binding pocket of BVDV RdRp via a structure-based virtual screening approach. One of them, N-(2-morpholinoethyl)-2-phenylquinazolin-4-amine (1, EC50= 9.7 ± 0.5 µM), was selected to perform different chemical modifications. Among twenty-four derivatives synthesized, eight of them showed considerable antiviral activity. Molecular modeling of the most active compounds showed that they bind to a pocket located in the fingers and thumb domain in BVDV RdRp, which is different from that identified for other non-nucleoside inhibitors (NNIs) such as thiosemicarbazone (TSC). We selected compound 2-(4-(2-phenylquinazolin-4-yl)piperazin-1-yl)ethanol (1.9; EC50= l.7 ± 0.4 µM) for further analysis. Compound 1.9 was found to inhibit the in vitro replication of TSC-resistant BVDV variants, which carry the N264D mutation in the RdRp. In addition, 1.9 presented adequate solubility in different media and a high stability profile in murine and bovine plasma.